Growth and Long-Run Sustainability - Robert D. Cairns; Vincent Martinet (Center for Economic Studies and ifo Institute (CESifo), 2019)
From any state of economic and environmental assets, the maximin value defines the highest level of utility that can be sustained forever. Along any development path, the maximin value evolves over time according to investment decisions. If the current level of utility is lower than this value, there is room for growth of both the utility level and the maximin value. For any resource allocation mechanism (ram) and economic dynamics, growth is limited by the long-run level of the maximin value, which is an endogenous dynamic sustainability constraint. If utility reaches this limit, sustainability imposes growth to stop, and the adoption of maximin decisions instead of the current ram. We illustrate this pattern in two canonical models, the simple fishery and a two-sector economy with a nonrenewable resource. We discuss what our results imply for the assessment of sustainability in the short- and the long-run in non-optimal economies.
Keywords: O44; Q56; 330; sustainable development; sacrifice; growth; maximin value; sustainability improvement; resource allocation mechanism; non-optimal economies